Efektivitas Konseling Individual Dengan Teknik Cognitive Defusion Dalam Meningkatkan Kepercayaan Diri Mahasantri - Mujahidah, Izzah; Suharmawan, Wahid; Mawaddati, Ika Romika (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Individuals with high self-confidence tend to exhibit various positive behaviors that support their ability to express opinions, make decisions, and build healthy social relationships, which are important for students at the Ibnu Katsir 2 Islamic Boarding School in Jember. The purpose of this study was to test the effectiveness of individual counseling services using cognitive defusion techniques in enhancing the self-confidence of students at Ibnu Katsir 2 Jember Islamic Boarding School. The research method used was a one-group pretest-posttest design, with the population consisting of students at Ibnu Katsir 2 Jember Islamic Boarding School, and a sample of 7 students selected purposively. The results obtained from this study show that the Asymp. Sig. (2-tailed) value is 0.018, which is below the reference standard of 0.05. Thus, it is concluded that there is a significant difference in the students' scores, indicating that counseling using the Cognitive Defusion technique is effective in enhancing the self-confidence of the students.